2019
DOI: 10.1002/hrm.21947
|View full text |Cite
|
Sign up to set email alerts
|

Subsidiary staffing, cultural friction, and subsidiary performance: Evidence from Korean subsidiaries in 63 countries

Abstract: Drawing from the notion of cultural friction and based on the agency theory rationalization of multinational enterprise (MNE) headquarter–subsidiary relationship, we examine the impact of cultural friction in foreign subsidiaries on subsidiary performance. We argue that cultural friction, arising due to a high presence of parent country nationals (PCNs) in culturally distant locations, has a detrimental effect on subsidiary performance. This effect is the strongest when the cultural friction is at the top mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 113 publications
(190 reference statements)
0
37
1
Order By: Relevance
“…Also, when investigating subnational cultures, scholars may expand their understanding by using other cultural frameworks such as the GLOBE study (House et al 2004), Ingelhart's World Value Survey (1997), the Schwartz Values Survey (1994) and the like. Finally, these within-country and cross-country cultural differences can affect subsidiary staffing and cultural friction in local subsidiaries of foreign companies in China; thus such research may have important applications and use (Singh et al 2019).…”
Section: Cultural Challengesmentioning
confidence: 99%
“…Also, when investigating subnational cultures, scholars may expand their understanding by using other cultural frameworks such as the GLOBE study (House et al 2004), Ingelhart's World Value Survey (1997), the Schwartz Values Survey (1994) and the like. Finally, these within-country and cross-country cultural differences can affect subsidiary staffing and cultural friction in local subsidiaries of foreign companies in China; thus such research may have important applications and use (Singh et al 2019).…”
Section: Cultural Challengesmentioning
confidence: 99%
“…The notion of cultural friction is relatively new to the international management literature that evaluates culture as a key element of cross-national differences. The general idea in this stream of literature is that the cultural difference between the home and the host country is the main issue for foreign subsidiary management (Singh et al , 2019). Cultural distance is often used as a measure of environmental complexity to examine strategic issues such as how home and host country differences influence employment designs (Gaur et al , 2007).…”
Section: Workaholism; the Role Of Culturementioning
confidence: 99%
“…Unlike cultural distance, cultural friction emphasizes the actual cultural contact between the interchanging entities in an environment where multilevel yet intertwined cultural differences arise simultaneously. It is to be noted that the interaction between individuals and organizations from culturally diverse countries has the potential for creating and developing a shared understanding and thus declining the possible conflicts between them (Singh et al , 2019).…”
Section: Workaholism; the Role Of Culturementioning
confidence: 99%
“…Employees who are able to maintain two different cultures are associated with high psychological adjustment ( Chen et al, 2008 ) and positive attitudes ( Wagstaff et al, 2020 ). On the other hand, some studies assert the presence of more than one culture in an organization has a detrimental effect ( Kadam et al, 2020 ) on employee behavior such as performance ( Singh et al, 2019 ). In a study conducted by Wagstaff et al (2020) on the bicultural identity and cultural intelligence of employees, they found an increase in the positive attitudes of individuals with two cultural identities.…”
Section: Acculturation and Organizational Socializationmentioning
confidence: 99%